Key Success Factor Tata Kelola Kota Tangguh Bencana - Novita, Asti Amelia (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
This paper examines the critical factors of governance for disaster resilient cities in the world through a literature study. Cities have experienced a culmination point where urban carrying capacity has weakened to ensure the resilience of urban communities. The weakening of the city's carrying capacity is due to natural factors such as climate change and artificial factors, such as inadequate land management and infrastructure. Referring to the urgency of city resilience to ensure community resilience to disasters, cities in various parts of the world have tried to increase resilience from various sides, including institutional resilience, economic resilience, social resilience, infrastructure resilience, and resilience.